Esistenza minima Stanze, spazî della mente, reliquiario - Pisaniello, Saverio (Strumenti per la didattica e la ricerca, 2008)
Esistenza minima brings together the results of a study carried out by the author in connection with his degree thesis. A celebrated pre-text - the letter of Pliny the Younger to Gallus in which he describes the Laurentian villa - becomes the mesh into which he weaves the pivotal figures of modernity. The continual cross-referencing of word and drawing, word and image, builds into a procedural approach that clearly posits the design dimension as the cognitive foundation. It is a singular, somewhat unusual text that transports the reader into a territory where the common ground between narration and memoir, the work of the masters and the personal diary, is intriguingly explored.